Governing AI in an Age of Global Challenges: A Sociotechnical Reflection of the Ethics of Sensitive Data - Anabela da Conceição Pereira (Technology in the Face of Global Challenges. ESA RN24/SSTNET Midterm Conference – Faculty of Arts and Humanities, University of Porto, November 26-27, 2025, Porto, Portugal, 2025)
The rapid adoption of AI technologies, accelerated by world crises such as the COVID-19 pandemic and war(s), has revealed tensions between technological innovation and social ethics. This paper critically examines the use of biometric, personal, and sensitive data in AI systems, with a focus on vulnerabilities related to privacy and consent. We reflect on the role of governance frameworks, including the European Union’s Artificial Intelligence Act, as a regulatory response, and assess their role in mitigating risks associated with current AI systems. Our contribution is the proposal of a model for shared governance that integrates regulation, digital literacy, and corporate and individual responsibility, aiming for more equitable technological innovation. By situating data governance within the sociology of science and technology, this proposition provides a foundational conceptualization of how societies can shape the development of AI to address global challenges in an ethical and just manner.